2017
DOI: 10.5943/mycosphere/8/8/2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of antibacterial and antibiofilm activity properties of Hypogymnia tubulosa (Schaer.) Hav. lichen extracts from different locations in Turkey

Abstract: The levels of bioactivity in lichens can change in response to environmental stress. For this reason, it was decided to compare the activity levels of Hypogymnia tubulosa (Schaer.) Hav. (Parmeliaceae) samples collected from six different localities in Turkey and the factors that may be effective. We also questioned our opinion that antibacterial activity is not directly proportional to the effectiveness of the antibiotic. The in vitro antibacterial activity and antibiofilm effect of diethyl ether (DE) and chlo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Extracts and isolated compounds from different lichen species antimicrobial activities. From literature surveys, it was found that lichen genus such as Usnea, Parmelia, Parmotrema, Cetraria, Pseudevernia and Hypogymnia showed potent antimicrobial and antifungal activities (Türk et al 2006;Kamal et al 2015;Özyiğitoğlu et al 2017). The major metabolites gyrophoric acid (1), stenosporic acid (2) isolated from the lichen, Xanthoparmelia pokornyi showed antimicrobial activity towards some known food borne bacteria and fungi.…”
Section: Biological Activity Of Orcinol Based Lichen Secondary Metabo...mentioning
confidence: 99%
“…Extracts and isolated compounds from different lichen species antimicrobial activities. From literature surveys, it was found that lichen genus such as Usnea, Parmelia, Parmotrema, Cetraria, Pseudevernia and Hypogymnia showed potent antimicrobial and antifungal activities (Türk et al 2006;Kamal et al 2015;Özyiğitoğlu et al 2017). The major metabolites gyrophoric acid (1), stenosporic acid (2) isolated from the lichen, Xanthoparmelia pokornyi showed antimicrobial activity towards some known food borne bacteria and fungi.…”
Section: Biological Activity Of Orcinol Based Lichen Secondary Metabo...mentioning
confidence: 99%